Situation Report: Bulgaria, 16 January 1984 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Lyudmila's Cult Survives Sweeping Changes in Party and Government / by Rada Nikolaev New Appointments in State Planning Committee / by Rada Nikolaev Guidelines on Administrative and Legal Services / by Rada Nikolaev The Balkan Nuclear-Free Zone Revisited / by Patrick Moore